Elección de concha en Coenobita compressus (Decapoda: Coenobitidae) - Guillén, Fedro Carlos; Osorno, José Luis (Revista de Biología Tropical, 1993)
Gasteropod shell preferences were anaiysed in 945 herrrut crabs (Coenobila compressus) from Isla Isabel, Nayarit, México (210 52' 30"N, 105' 54'W) durlng the dry (January) and rainy (July) seasons. The crabs selected significantly more Nerita scabricosta than any other of the eleven shell species used. Laboratory tests conflffi1ed such a preference. Apparently N. scabricosla gives !he maximum benefits to crabs as a result of its low weight-high volume relationship which is favoured when high mobility is needed and !he predation pressures are low.